The Effect of Jigsaw II Cooperative Learning Strategy on Developing Social Tolerance Among a Sample of 10th Basic Grade Students at Irbid City - Khazali, Qasem; Momani , Abdellateef; Melhem, Mohammad (Jordan Journal of Educational Sciences, 2016)
The current study aimed to reveal the effectiveness of the Jigsaw II cooperative learning strategy on developing the social tolerance among a sample of 10th grade students at Irbid city. To achieve the study objective were chosen four classes consisted of 81 students, including two male and two female sections were distributed randomly to two groups: the experimental and the control groups. The experimental group was taught according to Jigsaw II strategy in the courses of Arabic Language, Islamic Education and Geology. The researchers developed the social tolerance scale, which consists of 29 items and verified its validity and reliability. The results of the 2–Way ANCOVA analyses Showed that there were significant differences in the social tolerance scores due to the group in the experimental group fever. There were no significant differences in the social tolerance scores due to gender or the interaction between group and gender